Integrability of nonlinear dynamical systems and differential geometry structures - Samoilenko, V. G. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
Some aspects of the application of differential geometry methods to the study of the integrability of non-linear dynamical systems given on infinite-dimensional functional manifolds are considered.